Predictive Value of Cardiopulmonary Exercise Testing Parameters in Ambulatory Advanced Heart Failure - Lala, Anuradha; Shah, Keyur B; Lanfear, David E; Thibodeau, Jennifer T; Palardy, Maryse; Ambardekar, Amrut V; McNamara, Dennis M; Taddei-Peters, Wendy C; Baldwin, J Timothy; Jeffries, Neal; Khalatbari, Shokoufeh; Spino, Cathie; et al. (JACC. Heart failure, 2021)
This study sought to determine cardiopulmonary exercise (CPX) predictors of the combined outcome of durable mechanical circulatory support (MCS), transplantation, or death at 1 year among patients with ambulatory advanced heart failure (HF). Optimal CPX predictors of outcomes in contemporary ambulatory advanced HF patients are unclear. REVIVAL (Registry Evaluation of Vital Information for ventricular assist devices [VADs] in Ambulatory Life) enrolled 400 systolic HF patients, INTERMACS (Interagency Registry for Mechanically Assisted Circulatory Support) profiles 4-7. CPX was performed by 273 subjects 2 ± 1 months after study enrollment. Discriminative power of maximal (peak oxygen consumption [peak VO ]; VO pulse, circulatory power [CP]; peak systolic blood pressure • peak VO ], peak end-tidal pressure CO [PEtCO ], and peak Borg scale score) and submaximal CPX parameters (ventilatory efficiency [VE/VCO slope]; VO at anaerobic threshold [VO AT]; and oxygen uptake efficiency slope [OUES]) to predict the composite outcome were assessed by univariate and multivariate Cox regression and Harrell's concordance statistic. At 1 year, there were 39 events (6 transplants, 15 deaths, 18 MCS implantations). Peak VO , VO AT, OUES, peak PEtCO , and CP were higher in the no-event group (all p < 0.001), whereas VE/VCO slope was lower (p < 0.0001); respiratory exchange ratio was not different. CP (hazard ratio [HR]: 0.89; p = 0.001), VE/VCO slope (HR: 1.05; p = 0.001), and peak Borg scale score (HR: 1.20; p = 0.005) were significant predictors on multivariate analysis (model C-statistic: 0.80). Among patients with ambulatory advanced HF, the strongest maximal and submaximal CPX predictor of MCS implantation, transplantation, or death at 1 year were CP and VE/VCO respectively. The patient-reported measure of exercise effort (Borg scale score) contributed substantially to the prediction of outcomes, a surprising and novel finding that warrants further investigation. (Registry Evaluation of Vital Information for VADs in Ambulatory Life [REVIVAL]; NCT01369407).